Extracellular vesicles in cardiovascular diseases: pathogenic mediators, diagnostic tools, and therapeutic vectors - Li, Tianyi; Wang, Wan; Qin, Zilu; Chen, Yiling; Zhu, Kangjie; Liu, Haoyu; Sun, Jiangjiang; Zhong, Hongpeng (Frontiers in Cardiovascular Medicine, 2025)
Cardiovascular diseases (CVDs), the leading global cause of mortality, underscore an urgent need for innovative diagnostic and therapeutic strategies. Extracellular vesicles (EVs)—lipid-bilayer nanoparticles transporting bioactive cargo (microRNAs, proteins, lipids)—are critical mediators of intercellular communication in CVD pathogenesis. They exhibit functional duality: propagating pathology (inflammation, fibrosis, thrombosis) while facilitating tissue repair. This review synthesizes EV biogenesis mechanisms, isolation methodologies, source-specific functions, and multifaceted roles in atherosclerosis, myocardial infarction, heart failure, and stroke. We further evaluate EV-based diagnostic biomarkers, engineered therapeutic applications, clinical translation challenges, and future directions.